An Evaluation of the Antibacterial Activity of Pterocarpus tinctorius Bark Extract against Enteric Bacteria That Cause Gastroenteritis. (27th September 2022) - Mphande, Isaac; Kataba, Andrew; Muzandu, Kaampwe; Gono-Bwalya, Angela
Abstract : Enteric bacteria are the leading cause of bacterial gastroenteritis worldwide, particularly in low-income countries. The bark decoction of Pterocarpus tinctorius (Fabaceae) has traditionally been used to treat bacterial gastroenteritis. However, studies reporting the antibacterial activity of Pterocarpus tinctorius are rare. Therefore, this study aimed to evaluate the antibacterial activity of stem bark extract of Pterocarpus tinctorius against Escherichia coli, Salmonella typhi, and Shigella dysenteriae . The powdered bark extract was successively extracted with methanol using the cold continuous maceration method, followed by partitioning the crude methanolic extract to obtain methanolic, hexane, and chloroform subextracts. Three fractions were isolated from the methanolic subextract using ordinary normal phase column chromatography. The antibacterial activity of the extracts and fractions was performed using the agar well diffusion method. The minimum inhibitory concentration (MIC) was determined using the agar well diffusion method. While, minimum bactericidal concentration (MBC) was obtained by the subculturing method. The methanolic subextract was the only extract that showed antibacterial activity against the tested bacteria, and its activity was highest on Shigella dysenteriae followed by Salmonella typhi and was least active on Escherichia coli, with mean inhibition zones of 14.3 ± 0.2, 13.7 ± 0.3, and 12.2 ± 0.1 at 200 mg/mL, respectively. Chloroform subextract showed antibacterial activity only on Shigella dysenteriae, while hexane subextract did not show antibacterial activity against all bacteria tested at 100 mg/mL and 200 mg/mL. Among the three subfractions of methanolic subextract, only one subfraction was active and had both mean minimum inhibitory concentration and a minimum bactericidal concentration against Escherichia coli at 1.25 mg/mL, Salmonella typhi at 1.25 mg/mL, and Shigella dysenteriae at 0.6 mg/mL. The findings of this study support the use of Pterocarpus tinctorius in traditional medicine. Therefore, purification and structural elucidation studies are highly recommended.